Acquired reactive perforating collagenosis triggered by trauma with eosinophilia: a case report and literature review - Liu, Jie; Zhao, Peng; Zhang, Xinzhong; Gao, Jie; Han, Haozhi; Qin, Junxia (Frontiers in Medicine, 2024)
Acquired reactive perforating collagenosis (ARPC) is a rare dermatological disorder condition defined by the perforation of altered collagen fibers through the epidermis. The presence of underlying conditions such as diabetes or renal disease is helpful in the ARPC diagnosis. Although skin rashes related to ARPC have been reported, the exact causative factors and mechanisms remain unclear. Here, we present a unique case of ARPC triggered by trauma in a 67-year-old male without concurrent systemic alterations. The diagnosis of ARPC with eosinophilia was made following comprehensive diagnostic testing, including clinical presentation, histological results, and blood tests, ruling out other possible diseases. Intriguingly, the histopathological examination revealed collagen penetration into the epidermis at different tissue sections. In addition, we reviewed existing literature on ARPC, which documented the causation. To help confirm the diagnosis, clinicians have to pay attention to traumatic triggers for ARPC and its rare manifestation with eosinophilia.
CRIS-Team Scopus Importer:2024-07-19
Keywords: ARPC; case report; eosinophilia; skin rash; traumatic trigger